The Role of Learning Management Systems in Fostering Higher-Order Thinking Skills and Creativity: An Integrative Review - Gunawan Gunawan; Lovy Herayanti; Baiq Nabila Saufika Zainuri; Ni Made Yeni Suranti (Indonesian Journal of Teacher Education, 2021)
Learning Management Systems (LMS) have evolved from simple administrative repositories into vital interactive spaces in modern digital education. However, a comprehensive synthesis of how these platforms foster advanced cognitive competencies remains fragmented. This integrative review synthesizes literature published between 2011 and 2020 to examine the role of LMS in fostering Higher-Order Thinking Skills (HOTS) and creativity in higher education. Applying purposive inclusion criteria, 22 peer-reviewed articles from national and international publications were selected and analyzed across four major thematic clusters. The findings demonstrate that LMS effectively stimulates HOTS and creativity when synergized with active learning models (e.g., blended learning, flipped classrooms, and STEAM) and supported by interactive features like asynchronous discussions, concept mapping, and augmented reality. Additionally, success depends significantly on psycho-pedagogical factors, including student engagement, creative content design, and system adaptivity, which also ensured educational continuity during the COVID-19 pandemic. This review concludes that LMS acts as a strategic pedagogical catalyst rather than a mere storage tool. Consequently, educators should design student-centered, collaborative digital tasks, while developers should prioritize adaptive architectures to fully support 21st-century skills.